Analysis and experience about the importance of mentoring in the academic environment - de Matos, Carla Maria Voitena; Vivan, Alessandra Melânia Gressana (Perspectivas em Análise do Comportamento, 2018)
The art of teaching, for the most part, is awakened when the individual is exercising another role, that of student. Generally, academics seek their models, aiding in the process of self-construction, both personal and professional. The federal law of 1968 guides the guidelines of higher education and regulates the role of monitor in higher institutions. This practice stimulates in the student the development of skills that can be used by him for a future position - teacher. The importance of highlighting the monitoring function, reported in this production, as an objective of this. To confirm this importance, a quantitative analysis was carried out with the academic production evaluations - weekly reports of the experiments, and a qualitative analysis with the self-assessments requested to the academics at the end of the semester. The monitoring took place in the course of Psychology of the institution FADEP - Faculty of Pato Branco, southwest of Paraná, within the discipline of Experimental Analysis of Behavior. It is also explained a brief compilation on Behaviorism and Experimental Psychology, components of the practical activities developed. Finally, we present the discussions and comparisons visualized in practice and present in the results. . These that show the importance of monitoring funcion to assist in the production and execution of the experiments, act that affects in the evaluation of reports, in a positive perspective.